KONSEP ADIL DALAM AL-QUR’AN - Setyawan (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
The Al-Qur'an is a guide of all time, the most appropriate and the most perfect so that if all the commands contained in it are enforced and carried out seriously by all parties, then every member of society will feel the joy of life. One of the concepts in the Koran is justice, the form of wisdom contained in it is realizing unity and brotherhood, fostering harmonious relationships and closeness among society. Apart from having a deep meaning, justice has various forms covering all aspects of life, such as: justice towards oneself, justice in the household, justice in society, justice in government and the judiciary, justice in guardianship, justice in the economy, justice in testimony, justice in peace, and justice even towards enemies.